EVALUASI BANJIR RANCANGAN PADA DESAIN SPILLWAY - Aditya Noor Rizqan; Holdani Kurdi; Novitasari Novitasari (INFO-TEKNIK, 2021)
The design of water structures in rivers is very necessary to be able to manage rivers. Water structures, for example dams and weirs can be selected to manage watersheds. This study aims to evaluate the Tapin Dam spillway. The analytical method used is in the form of hydrological analysis and the design of the main building and spillway accessories. Hydrological analysis used with analysis of the frequency of rain data. Calculation of design flood discharge using the Melchior method. Spillway hydraulic analysis used the USBR Small Dams method. The data used is from secondary data. Data in the form of rain data at the nearest station, dam technical data and topography. The results of hydrological and hydraulics analysis calculations, based on data analysis for 15 years at the Bungur Rain Station using the Gumber method, the 100 year return period design rain is 167.56 m3/sec. The peak Q calculation using the Melchior method for a 100 year return period is 417.15 m3/s, for a Tc concentration time of 11.86 hours. Based on the above results, the second conclusion from this study is that the hydraulic analysis obtained a discharge curve after a spillway, with an elevation of 147.5 m, a flow height above the crest as high as 2.00 m with a discharge of 165.20 m3/s.